Occurrence of halogenated contaminants in fish from selected river localities and ponds in the Czech Republic - Hrádková, Petra; Pulkrabová, Jana; Kalachová, Kamila; Hloušková, Veronika; Tomaniová, Monika; Poustka, Jan; Hajšlová, Jana (Archives of environmental contamination and toxicology, 2012)
The occurrence of organohalogenated compounds including major persistent chlorinated pollutants, such as polychlorinated biphenyls (PCBs) and DDT and its metabolites, brominated flame retardants (BFRs), represented by polybrominated diphenylethers (PBDEs) and hexabromocyclododecane (HBCD), together with currently widely discussed perfluorinated compounds (PFCs), mainly perfluorooctane sulfonic acid was monitored in several fish species collected from Czech rivers. Eleven sampling locations in highly industrialized areas were chosen. In addition, wild species of 14 farmed fish (grown in dedicated ponds) were also analysed. With respect to the contamination in different areas, chlorinated chemicals were dominant. PCBs and DDTs ranged from 4.8 to 211 and 2 to 791 μg/kg wet weight, respectively. Concentrations of BFRs and PFCs were significantly lower and ranged from 0.6 to 10.2 and 0.9 to 62 μg/kg wet weight, respectively. The highest levels of target analyte groups were found in fish muscle tissue in localities situated on the lower part of the Elbe River: Levels of DDT, HCB, PBDEs, and perfluorooctane sulfonic acid (PFOS) were as high as 791, 77.6, 14.4 and 193 μg/kg wet weight, respectively, in Usti nad Labem and in the sample originated from the confluence of Elbe with Bilina River; a sum of PCBs at a level of 211 μg/kg was detected.
Keywords: rybníky; chemické znečištění vody; Animals; Environmental Monitoring; Muscle, Skeletal; Ponds; ryby; vodní hospodářství; Czech Republic; Water Pollution, Chemical; zvířata; Hydrocarbons, Halogenated; kosterní svaly; řeky; Česká republika; Water Pollutants, Chemical; halogenované uhlovodíky; Aquaculture; Rivers; chemické látky znečišťující vodu; monitorování životního prostředí; Fishes